2019
DOI: 10.3390/ijms21010248
|View full text |Cite
|
Sign up to set email alerts
|

The Role of EjSPL3, EjSPL4, EjSPL5, and EjSPL9 in Regulating Flowering in Loquat (Eriobotrya japonica Lindl.)

Abstract: The age pathway is important for regulating flower bud initiation in flowering plants. The major regulators in this pathway are miR156 and SPL transcription factors. To date, SPL genes have been identified in many species of plants. Loquat, as a woody fruit tree of Rosaceae, is unique in flowering time as it blooms in winter. However, the study of its SPL homologous genes on the regulation mechanism of flowering time is still limited. In this study, four SPL homologs—EjSPL3, EjSPL4, EjSPL5, and EjSPL9—are clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 72 publications
2
23
0
Order By: Relevance
“…Furthermore, AP2 is regulated by LFY, and plays a central role in promoting floral meristem determinacy [32][33][34]. Previously, it was also reported that FT, SOC1, SPL4, SPL5, and SPL9 orthologs are upregulated in flower bud differentiation in loquat [2,35,36]. These similar results indicate that the RNA-Seq data and expression changes of the DEGs involved in floral transition are reliable in our study.…”
Section: Key Genes Of Tfs and Floral Integrators Associated With Flowsupporting
confidence: 87%
“…Furthermore, AP2 is regulated by LFY, and plays a central role in promoting floral meristem determinacy [32][33][34]. Previously, it was also reported that FT, SOC1, SPL4, SPL5, and SPL9 orthologs are upregulated in flower bud differentiation in loquat [2,35,36]. These similar results indicate that the RNA-Seq data and expression changes of the DEGs involved in floral transition are reliable in our study.…”
Section: Key Genes Of Tfs and Floral Integrators Associated With Flowsupporting
confidence: 87%
“…4 ). These results were observed throughout the life cycles of wild type and rga1 mutants, which is in line with the earlier reports 29 , 30 . To understand the role of RGA1 in the tiller development, we developed protein–protein interaction networks using experimentally validated interactors reported in tillering phenotypes in rice.…”
Section: Resultssupporting
confidence: 93%
“…At the physiological level, the processes regulated by Gα include ABA mediated stomatal opening 21 , stomatal density regulation 22 , sphingolipid signaling 23 , sugar signaling 24 , light-stimulation of nitrate reductase gene expression 25 and phenylalanine and ABA production 26 , 27 . In rice, the reported roles of Gα include abiotic stresses 28 including salt stress 29 , drought 30 , photo-oxidation 31 , plant immunity 32 , plant growth 33 , grain size 34 , nitrate response 35 and brassinosteroid signaling 13 , 36 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers also found that the expression of SPLs decreased under heavy fruit load in Citrus clementina , and Citrus SPL was able to promote flowering independent of photoperiod in Arabidopsis [ 13 ]. EjSPL4, EjSPL5, and EjSPL9 could significantly activate the promoters of EjSOC1-1 , EjLFY-1 , and EjAP1-1 in loquat and the over-expression of EjSPL3 , EjSPL4 , EjSPL5 , and EjSPL9 in A. thaliana could promote obvious flowering [ 14 ]. However, the hierarchical action of miR156 in vegetative phase growth in perennial woody plants is still unknown.…”
Section: Introductionmentioning
confidence: 99%